2024
DOI: 10.1021/acs.inorgchem.4c00985
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doped Ni2P/NiSe2 Composite Catalysts for Urea Oxidation Reaction (UOR) for Energy-Saving Hydrogen Production by UOR-Assisted Water Splitting

Chen-Jin Huang,
Qi-Ni Zhan,
Hui-Min Xu
et al.

Abstract: The development of efficient urea oxidation reaction (UOR) catalysts helps UOR replace the oxygen evolution reaction (OER) in hydrogen production from water electrolysis. Here, we prepared Fe-doped Ni 2 P/NiSe 2 composite catalyst (Fe−Ni 2 P/NiSe 2 -12) by using phosphating-selenizating and acid etching to increase the intrinsic activity and active areas. Spectral characterization and theoretical calculations demonstrated that electrons flowed through the Ni−P−Fe−interface− Ni−Se−Fe, thus conferring high UOR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…169 In addition, it should also be rigorously demonstrated that the synergistic effect of heterostructures can produce a “1 + 1 > 2” effect. For example, Jiang et al 170 demonstrated that the performance of one-component mechanical mixing was much inferior to that of heterostructures, and Huang et al 171 used ECSA normalization curves to prove that the intrinsic activity of heterostructures was stronger than that of one-component structures.…”
Section: Discussionmentioning
confidence: 99%
“…169 In addition, it should also be rigorously demonstrated that the synergistic effect of heterostructures can produce a “1 + 1 > 2” effect. For example, Jiang et al 170 demonstrated that the performance of one-component mechanical mixing was much inferior to that of heterostructures, and Huang et al 171 used ECSA normalization curves to prove that the intrinsic activity of heterostructures was stronger than that of one-component structures.…”
Section: Discussionmentioning
confidence: 99%